Perancangan Desain UI/UX Berbasis Scan Barcode Dengan Metode Design Thinking Untuk Pemesanan Makanan - Ahmad Rayhaan Yusri; Isa Faqihuddin Hanif; Muhammad Daffa Al-farel; Muhammad Naufalrio Zaandami; Muhammad Yasin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
For those who want an authentic taste of the typical Tegal cuisine, Warkop Bu Haji is the top choice theme. They can enjoy gourmet gourmets as well as traditional drinks such as coffee, tea, and fresh drinks with naturally produced fruits. Warkop Mother Haji wants to use new technology to improve service for operations and customer experience. Warp owners are looking for creative solutions in this digital age, when the demand for ease and speed of ordering food is rising. The focus of the research is a food ordering system that uses barcode scanning and the latest technology to improve the user experience. By using a mobile device to scan the barcode on the table, customers can easily order food. We work hard to ensure that our customers have a satisfactory and effective experience. Due to technological developments and changing consumer preferences, digital food ordering apps are becoming increasingly popular. This research is important because it allows customers to order food easily and quickly. User/User Interface (UI/UX) design and technical functionality are crucial. The research uses the Design thinking Method, which prioritizes users in innovative solutions. Prototype research involved 15 customer respondents and 1 partner respondent. The prototype design value for the customer was 86.6%, and the customer questionnaire score was 97.1%. The prototipe design score for the partner was 90%, and partner questionnary value was 91.6%. The research is expected to be beneficial to Warkop Mother Haji and industry. With a better customer experience, it is expected to improve the reputation and expand the customer base.